Conceptual basis for the search and eco-diagnostics of risk zones in watersheds - M. T. Мykytsei (Людина і довкілля: Проблеми неоекології)
Purpose. To develop and substantiate the conceptual basis of a new approach for ecological diagnostics of anthropogenic soil (land) pollution in “risk-critical zones” of ecological soil-water interactions within watersheds. This approach aims to optimize the integrated ecological management system, enhance nature protection, and improve environmental safety in Ukraine.